Policy Analysis of the Zoning System and Its Implications for Student Resilience, Self-Efficacy and Learning Achievement in Public SMP in Gresik District - Sri Mulyaningsih; Mufarrihul Hazin; Haris Supratno (Dinasti International Journal of Education Management And Social Science, 2025)
The zoning policy in Indonesia's education system is implemented to equalize access to education in all regions and reduce inequality between schools. This study aims to analyze the impact of the zoning policy on student resilience, self-efficacy, and learning achievement in public junior high schools in Gresik Regency. The method used in this research is a qualitative approach with a literature study, collecting data from various literature sources such as books, scientific articles, journals and related policy documents. The results show that the zoning policy has a positive impact on students' emotional resilience, improving social interaction between students and creating more equitable educational opportunities. However, it also poses challenges for schools with limited facilities that have to improve teaching quality to meet students' and parents' expectations. The impact on students' self-efficacy depends on school facilities and students' perceptions of the school they choose. Overall, the zoning policy can improve learning achievement if it is followed by improvements in the quality of education in all schools.